1990
DOI: 10.1288/00005537-199010000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Le fort i osteotomy approach to the skull base

Abstract: Horizontal osteotomy allows the surgeon to safely down‐fracture the maxilla for wide exposure of the central skull base. This surgical approach is easily extended posteriorly in the midline to include the clivus and the arch of C1, providing 8 cm of horizontal anterior exposure and 5 cm of posterior. Wide operative exposure and a low rate of complications afford superior functional and cosmetic preservation in removing tumors of the central cranial base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…88,96,100 A sublabial incision allows a horizontal osteotomy and down-fracture or inferior mobilization of the maxilla and hard palate to be performed. Others have described this approach as the "drop-down" maxillotomy approach.…”
Section: Le Fort I Osteotomy With Down-fracture Of Maxillamentioning
confidence: 99%
“…88,96,100 A sublabial incision allows a horizontal osteotomy and down-fracture or inferior mobilization of the maxilla and hard palate to be performed. Others have described this approach as the "drop-down" maxillotomy approach.…”
Section: Le Fort I Osteotomy With Down-fracture Of Maxillamentioning
confidence: 99%
“…72 The major transpalatal approach-related concerns are the development of a palatal fistula or wound dehiscence. 109 Lewark, et al, 72 performed Le Fort I osteotomies in 11 children and reported related complications including loss of unerupted tooth buds and epiphora in one case each. Disruption of facial growth was assumed to be unlikely because the osteotomy did not pass through growth centers.…”
Section: Neurosurg Focus / Volume 12 / May 2002mentioning
confidence: 99%
“…This can be reduced by utilising one of the anterior corridors of access (e.g. : transoral [13], transmaxillary [5,40,42], transsphenoidal, transantral and transmandibular [8,33]) and many of these techniques have been advocated in the management of basilar aneurysms and other central skull base lesions. However, in general these approaches are Intracranial target = basilar bifurcation.…”
Section: Minimise or Eliminate Brain Retractionmentioning
confidence: 99%
“…When utilised to gain access to high basilar bifurcation aneurysms the low anterolateral corridor of approach allows the surgeon to combine the advantages of the anterior approach of better visualisation of both P1 segments of the posterior cerebral arteries [5,42], with those of a lateral approach providing improved access to the vital posterior perforating arteries to the midbrain [16,17,38,39,41,56,58].…”
Section: Isolation and Protection Of Surrounding Neurovasculaturementioning
confidence: 99%